2022
DOI: 10.1002/mp.16042
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of CT‐based radiomics nomogram for the classification of benign parotid gland tumors

Abstract: Purpose Accurate preoperative diagnosis of parotid tumor is essential for the formulation of optimal individualized surgical plans. The study aims to investigate the diagnostic performance of radiomics nomogram based on contrast‐enhanced computed tomography (CT) images in the differentiation of the two most common benign parotid gland tumors. Methods One hundred and ten patients with parotid gland tumors including 76 with pleomorphic adenoma (PA) and 34 with adenolymphoma (AL) confirmed by histopathology were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that radiomic research using CT and MR images performs well in differentiating PA and AL. Zheng ( 25 ) gathered 76 instances of PA and 34 cases of AL and built a model based on CT images with an AUC of 0.89 and an accuracy of 83.3%. Song ( 26 ) built a T1-2WI model based on MR images with an AUC of 0.90 and an accuracy of 86% after collecting 140 instances of PA and 112 cases of AL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that radiomic research using CT and MR images performs well in differentiating PA and AL. Zheng ( 25 ) gathered 76 instances of PA and 34 cases of AL and built a model based on CT images with an AUC of 0.89 and an accuracy of 83.3%. Song ( 26 ) built a T1-2WI model based on MR images with an AUC of 0.90 and an accuracy of 86% after collecting 140 instances of PA and 112 cases of AL.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this prognostic model has certain clinical applicability. Zheng ( 25 ) developed and validated a novel prognostic model using a nomogram-based approach to differentiate between PA and AL. This model incorporated the CT Rad-score and independent clinical factors.…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing images using radiomics method, molecular level information contained in images could be obtained. It could assist clinicians to make independent treatment plans for patients [19]. Chest enhanced CT images were analyzed by radiomics, and different image features had signi cant effect in predicting the expression level of molecular biological marker Ki-67, and could guide clinical treatment and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral alveolar echinococcosis is a rare parasitic disease, but it is still a severe public health issue in many parts of the world. We believe that radiomics based machine learning is a novel tool to investigate this disease, which have been proved as a powerful approach in other elds [33][34][35][36] .…”
Section: Discussionmentioning
confidence: 99%